Equity And Accountability: Harassment And Electronic Crimes at Workplace in Pakistan, Its Physio-Psychological Effect on Victims, And Role of Legislative Initiatives to Prevent the Curse - Ghulam Abbas; Maiha Kamal; Ghulam Rasool Zahid; Sundas Bashir; Muhammad Asif Naveed; Seemab Jaffery; Muhammad Imran; Humaira Farah; Umar Farooq; Umair Mahmood; Muhammad Farooq Khalid; Muhammad Auon; et al. (International Journal for Electronic Crime Investigation, 2024)
Electronic crimes, such as cyberbullying are major contributors to workplace harassment in Pakistan, affecting the mental and physical health of victims. Such crimes create a toxic work environment, reducing productivity. Harassment in Pakistan is a societal issue that, with its deep-rooted cultural, institutional, and legislative difficulties, is ever-prevalent. This has not only undermined the self-respect and well-being of victims but also has caused deep physio-psychological effects. Individuals of workplace harassment experience a series of physical as well as psychological symptoms such as anxiety, stress-related disorders, depression, and weakened self-esteem leading to declined job satisfaction, increased absenteeism, and lower performance causing great challenges for individuals and organizations. The socio-cultural perspective of Pakistan, with its gender norms and ordered structures, worsens the problem, especially for women and downgraded groups. The harassment incidents are usually underreported due to social humiliation, insufficient support systems, and fear of revenge. Also, lack of training and awareness on workplace conduct and the rights of workers cause a culture of liberty for criminals. To address the harassment challenges, Pakistan has taken legislative initiatives like the Protection Against Harassment of Women at the Workplace Act, of 2010. The Act supports handling complaints and sets out punishments for culprits of harassment. However, despite the legislative measures, and awareness programs the effective execution/implementation of laws remained a major challenge due to which harassment is rapidly prevailing in Pakistani society, particularly targeting women and poor people populations. Most organizations lack the essential infrastructure and/or commitment to completely obey these guidelines. Therefore, there is a need for continuous training and education to nurture a workplace culture that upholds equality and respect. Supporting networks for the victims and cybercrime awareness campaigns can play an important role in inspiring more individuals to come forward for justice. Enhancing the capacity of institutions to implement these laws, promoting gender-sensitive training, and fostering an inclusive workplace culture is crucial for mitigating the physio-psychological impacts of harassment and ensuring a safe and equitable work environment for all employees. Existing legislation addresses cybercrime and harassment, but stronger policies are needed to protect workers better. This paper explores the impact of electronic crimes on workplace harassment and legislative efforts to address these issues.